2016
DOI: 10.1007/s10853-016-9909-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbonation behavior of hydraulic and non-hydraulic calcium silicates: potential of utilizing low-lime calcium silicates in cement-based materials

Abstract: This paper presents a study on the carbonation behaviors of hydraulic and nonhydraulic calcium silicate phases, including tricalcium silicate (3CaOÁSiO 2 or C 3 S), c-dicalcium silicate (c-2CaOÁSiO 2 or c-C 2 S), b-dicalcium silicate (b2CaOÁSiO 2 or b-C 2 S), rankinite (3CaOÁ2SiO 2 or C 3 S 2 ), and wollastonite (CaOÁSiO 2 or CS). These calcium silicate phases were subjected to carbonation reaction at different CO 2 concentration and temperatures. Thermogravimetric analysis (TGA) tests were performed to quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(95 citation statements)
references
References 62 publications
11
64
2
Order By: Relevance
“…The silicate phases reported by other researchers, such as C–S–H [9,10,11], calcium silicate hydrocarbonate [12], or Ca-modified silica gel [14], were not found in this study. Figure 16 shows the molecular structure of C 3 S, C–S–H, amorphous SiO 2 , and different Q n in their structure.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The silicate phases reported by other researchers, such as C–S–H [9,10,11], calcium silicate hydrocarbonate [12], or Ca-modified silica gel [14], were not found in this study. Figure 16 shows the molecular structure of C 3 S, C–S–H, amorphous SiO 2 , and different Q n in their structure.…”
Section: Discussioncontrasting
confidence: 67%
“…Shtepenko et al [13] used 29 Si magic angle spinning–nuclear magnetic resonance ( 29 Si MAS-NMR), XRD and a scanning electron microscope coupled with an energy dispersive spectrometer (SEM-EDS) to analyze the carbonation of β-dicalcium silicate (β-C 2 S), and concluded that polymerized silica, calcite, and aragonite were the main products. Ashraf and Olek [14] believed that Ca-modified silica gel and CaCO 3 crystal were the main products of C 3 S carbonation. From the above studies, it was indicative that the carbonation products of C 3 S could be classified into two phases: silica phase and calcium carbonate phase.…”
Section: Introductionmentioning
confidence: 99%
“…Chemicals such as NaOH can be added to accelerate and enhance the process even further [7]. Most recent research developments in producing CO 2 uptake cements depart from calcium (and magnesium)-rich materials and relate to 1) accelerated curing of concrete [8][9][10], 2) carbonation of brines [11][12][13], 3) carbonation of hydrated lime [14,15] and 4) carbonation of calcium silicates [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…To quantitatively assess the importance of mineralogy in CO 2 mineralization, Bodor et al 20) and Ashraf and Olek 21) reacted synthetic minerals common to slag using autoclave reactors. These mild conditions are consistent with processes that may result in net CO 2 Table 1, indicate ~2 orders of magnitude variation in PL thickness between the minerals studied.…”
Section: Mineralogy and Crystallinitymentioning
confidence: 99%
“…pres., 95% humidity, 20% CO2 § Data from Ashraf and Olek. 21) Experimental conditions: incubator reactor, 35°C, atm. pres., 94% humidity, 15% CO2 a: Tridymite; b: Cristobalite; c: Pseudowollastonite; d: Wollastonite; e: Calcite; f: Aragonite; g: Vaterite alization by less reactive species.…”
Section: Mineral Lockingmentioning
confidence: 99%